INEFFICIENT MARKETS, ANOMALIES, AND INVESTOR BEHAVIOR: A LITERATURE REVIEW - Nurdina Nurdina; R Yudi Sidharta; Mochamad Mochklas (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to observe and analyze the accounting literature which examines the phenomena that occur in inefficient markets. This article analyzes the effect of anomalies on investor behavior and stock returns. This study begins by identifying the effects of anomalies: 1) seasonal anomalies, 2) momentum anomalies. This article identifies investor behavior; 1) overreaction/ under reaction, 2) loss aversion, and 3) overconfidence. This study primarily evaluates how anomalous effects affect investor behavior towards stock returns. Within each category, this article analyzes the findings of previous research. Evidence from inefficient market research tends to help investors to reduce excessive behavior towards the effects of anomalies and help make investment decisions. This study examines opportunities for future research and research implications in capital markets.